Evaluation of safety and efficacy of the bone marrow mesenchymal stem cell and gelatin-nano-hydroxyapatite combination in canine femoral defect repair - Ma, Zihang; Guo, Xiaoying; Zhang, Jun; Jiang, Qifeng; Liang, Wuying; Meng, Wenxin; Chen, Shuaijiang; Zhu, Yufan; Ye, Cundong; Jia, Kun (Frontiers in Veterinary Science, 2023)
Femoral shaft fracture is a common bone trauma in dogs. The limitation of mesenchymal stem cells in bone defect applications is that the cell suspension cannot be fixed to the bone defect site. In the study, our objective was to substantiate the combined application of canine bone marrow mesenchymal stem cells (cBMSCs) and gelatin-nano-hydroxyapatite (Gel-nHAP) and evaluate its therapeutic effect on bone defect diseases in dogs. Experiments were performed to evaluate the following: (1) the porosity of Gel-nHAP; (2) the adhesion of cBMSCs to Gel-nHAP; (3) the effect of Gel-nHAP on cBMSC proliferation. The efficacy and safety of the combination of cBMSC and Gel-nHAP in the repair of femoral shaft defects were evaluated in animal experiments. The results showed that Gel-nHAP supported the attachment of cBMSCs and exhibited good biocompatibility. In the animal bone defect repair experiment, significant cortical bone growth was observed in the Gel-nHAP group at week 8 (P < 0.05) and in the cBMSCs-Gel-nHAP group at week 4 (P < 0.01). We demonstrated that Gel-nHAP could promote the repair of bone defects, and the effect of cBMSC-Gel-nHAP on the repair of bone defects was profound.